A case for thinking about thinking in sports coaching: Understanding situated cognition as a means to inform coaching practice - Quick, S.; Lyle, J.; Baghurst, T. (International Sport Coaching Journal, 2026)
Research in sports coaching has most often been conducted using one of a number of disciplinary lenses (e.g., psychological, sociological, philosophical, or physiological). Although acknowledging that these approaches have provided a valuable, if partial, insight into aspects of coaching practice, limitations inevitably exist when adopting singular disciplinary perspectives. This research explored the situated (i.e., in, through, and within social contexts) coaching cognitions of an ice hockey coach using an ethnographic approach and methodological bricolage to generate data over 7 months. Using iterative adaptive research cycles, findings revealed that cognitions are (a) shaped by their proximity to goals at different social layers, (b) influenced by the social exchange (i.e., power and relationships) in which they occur, and (c) underpinned by biographical experiences. This study contributes significantly to how coaches can understand how their cognitive processes form, shape, influence, and are influenced by the coaching environment. In turn, the findings presented in this study offer opportunities, or prompts, for coaches to examine how their cognitions are formed, shaped, and shared to inform their practice interventions.